Indonesia’s Strategic Engagement in G20: The Role of Economic Diplomacy in Advancing National Interests and Fostering Inclusive Global Economic Growth - Prasetyo, Bowo (LPPM Institut Bisnis dan Informatika Kesatuan, 2023)
Economic diplomacy as a key instrument in advancing national interests and supporting inclusive global economic development. G20, as a major economic forum involving both developed and developing nations, provides a strategic platform for Indonesia to participate in multilateral negotiations and cooperation. This research employs a qualitative approach, focusing on document analysis, literature review, and a comprehensive understanding of Indonesia’s role in G20. Relevant data were gathered from official sources, including Indonesia’s government statements, G20 documents, and B20 policy reports. The analysis aimed to identify Indonesia’s economic diplomacy strategies, the impact on economic growth, and efforts to build networks within G20. Indonesia, as a G20 member, not only conducts economic diplomacy for national interests but also contributes to a more inclusive and sustainable global development. The stable economic growth, supported by effective economic diplomacy strategies, has positioned Indonesia as a key player in shaping the G20 agenda. Through participation in G20, Indonesia facilitates constructive dialogue between the private sector and the government, strengthening synergy to achieve shared economic development goals. This research provides in-depth insights into Indonesia’s role in G20, emphasizing how economic diplomacy serves as a potent instrument for achieving national and regional success. The implications of these findings extend beyond the G20 context, offering perspectives on how developing countries can play a significant role in shaping a more equitable and sustainable global economic development.